Efforts to Build Discipline Character Through Audio Visual Media in Early Childhood - Setianingsih, Ambar; Asmawulan, Tri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe efforts to build discipline character through audio-visual media in Group A children of Aisyiyah Kadipiro III Kindergarten and to explore the challenges faced by teachers in utilizing such media effectively. Methodology: The research employed a qualitative descriptive approach. The subjects were Group A teachers and Group A children of Aisyiyah Kadipiro III Kindergarten. Data collection techniques included interviews, observations, and documentation. The data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing. Results: The study found that the formation of children's discipline character through audio-visual media was conducted by: (1) Playing educational videos about discipline; (2) Playing educational songs that promote discipline. Challenges encountered by teachers include: (3) Audio-visual learning often requires more preparation time; and (3) Long video durations can exceed children's attention spans, making it difficult to maintain engagement. Applications/Originality/Value: This study provides insight into how early childhood educators can leverage audio-visual media to instill discipline in young learners. It also highlights the practical challenges in media use, emphasizing the need for efficient planning and age-appropriate content selection. The findings can inform curriculum development and teacher training in early childhood education settings.